01 PEMBERDAYAAN ANGGOTA KELOMPOK TANI PADI MELALUI PENGUATAN MODAL USAHA DI DESA TUNIKAMASEANG KECAMATAN BONTOA KABUPATEN MAROS - Jurnal Agribis; Annisa Mutmainnah; Zulkifli Zulkifli; Mohammad Anwar Sadat (Jurnal Agribis, 2020)
Empowerment is an effort to provide reinforcement to the community. This research was carried out in Tunikamaseang Village, Bontoa District, Maros Regency, aimed to: 1. To find out the empowerment of members of rice farmers through strengthening business capital in Tunikamaseang Village, Bontoa District, Maros Regency 2. Analyzing the factors that influence the empowerment of members of rice farmers through strengthening capital business in Tunikamaseang Village, Bontoa Subdistrict, Maros Regency. The population in this study were farmers. A simple random sample of farmers was determined by 25 (twenty-five) farmers. Data was collected from the survey results using a questionnaire and supplemented with observations / field observations. The data collected was then tabulated to obtain real data used for analysis purposes. The results showed that the empowerment of members of rice farmers through strengthening business capital in Tunikamaseang Village, Bontoa District, Maros Regency consisted of two, namely (1) empowerment of farmer groups in Tuniamaseang Village, Bontoa District, was included in the medium category with a number of 63.73. (2) the regression factor where X1 is education of 0.034 Farmers, X2 where the experience of farming is 0.129, and X3 where there is an area of ​​land of 0.043.